Validity and Reliability of Pre-Service Teacher Competency Level in Teaching Early Mathematics Instrument Using the Rasch Model - Nordin, Norazly; Ghazali, Munirah; Radzali, Nur Faridatul Jamalia; Hashim, Nor Hashimah; Chear, Syed Lamsah Syed (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
The Pre-Service Competency Teacher Level in Teaching Early Mathematics Instrument has been developed to measure the competency level and readiness to teach early mathematics in Preschool. This study was conducted to produce empirical evidence on the validity and reliability of this instrument by using the Rasch model. Surveys were conducted in three private universities that offer Early Childhood Education Programmes. A total of 85 pre-service teachers were selected as a sample of the study through simple random sampling. The validity and reliability of the instrument were measured using Rasch's model through Winstep software version 3.68.2. The findings of the unidimensionality test showed 46.1%. The Rasch analysis shows the person reliability index is 0.8 with a separation index is 2.05. The item reliability index is 0.91 and the separation index is 3.18. The item fitness analysis found 29 items in the instruments are in the valid range and one item that falls out of the allowed range. The finding showed that this instrument has a high degree of validity and reliability and can be used to measure the competency level of pre-service teaching in teaching early mathematics.